Pengaruh Brand Experience, Brand Ambassador dan Brand Image Terhadap Brand Loyalty Scarlett Whitening - Kuwatno; Sitta Saraya; Lukman Zaini Abdullah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study looks into how brand experience, brand ambassadors, and brand image influence brand loyalty for Scarlett Whitening products in Kendal Regency. A total of 100 people who use Scarlett Whitening were included in the study. Information was gathered using an online survey on Google Forms. The data was analyzed using multiple linear regression with IBM SPSS 26 software, and responses were measured on a Likert scale. The findings show that brand experience, brand ambassadors, and brand image all have a strong and positive effect on brand loyalty for Scarlett Whitening in Kendal Regency. This is shown by the calculated F value of 99. 805, which is higher than the F table value of 2. 70, and a significance level of 0. 000.